Transformacja, tranzycja, okres przejścia. Białoruś przełomu wieków - Musiał, Miron J. (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The terminology developed to serve the needs of stableWestern democracies fails with respect to the republics that emerged following the collapse of the USSR. This may be confirmed by the notion of the ‘grey zone’, assisted democracy, managed democracy or electoral democracy. The Belorussian transition process seems to be work in progress. Its closure would demand that the current state be acknowledged as being stable rather than transitional. Aunanimous assessment is not assisted by the terminological divergence that is indispensably accompanying transformation, transition or the period of transition, as termed in the Russian language, which seems to be the best description of the process. The analysis does not apply the dichotomist approach to democracy, either, where democracy is considered to be either present or absent, since it is impossible to identify the nondemocratic elements of the system unanimously. T. Carothers, who was critical of Huntington’s Third Wave, claims that when the key elements of a political system are appropriately manipulated for the benefit of a heuristic analysis it results in a political system of managed democracy to be a priori acknowledged to be a democratic one. The tools of analysis developed for the needs of stableWestern democracies fail when faced with a new type of personal, party or military dictatorship, or with neoauthoritarianism, understood as authoritarianism altered by the irreversible globalization processes.